Labor relations : - Fossum, John A. (McGraw-Hill, 2006)
Labor Relations: Development, Structure, Processes discusses the history and development of labor relations, the structure of union organizations, union organizing and union avoidance, bargaining issues, and the process of negotiations and contract administration. As a result of decreasing union membership over the last twenty years, more material in the book addresses employee relations in nonunion organizations including examples of both cooperative and adversarial relationships.